2015
DOI: 10.1016/j.petrol.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Temperature nanotracers for fractured reservoirs characterization

Abstract: nanoparticle silica deoxyribonucleic acid (DNA) thermochromic inverse problem a b s t r a c t Nanoparticle tracers are being investigated as a potential tool to measure temperature distributions in subsurface reservoirs. If the temperature distributions could be measured more precisely, this would greatly enhance the ability to estimate other reservoir properties, which would in turn inform reservoir engineering and field management decisions. Work toward two distinct but parallel objectives are described here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Utilization of nanoparticles in reservoir characterization bears the promise of helping to overcome some of these issues, while offering many additional possibilities for the development of smart and versatile exploration tools. First and foremost, while being small enough to be able to flow through porous rock layers 15 , nanoparticles can still concentrate a substantial amount of molecules, making detection feasible while using much lower tracer amounts 16 . Moreover, multiple chemical markers can be incorporated into the same nanoparticles, enabling the addition of a stable background signal alongside a reporting signal 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of nanoparticles in reservoir characterization bears the promise of helping to overcome some of these issues, while offering many additional possibilities for the development of smart and versatile exploration tools. First and foremost, while being small enough to be able to flow through porous rock layers 15 , nanoparticles can still concentrate a substantial amount of molecules, making detection feasible while using much lower tracer amounts 16 . Moreover, multiple chemical markers can be incorporated into the same nanoparticles, enabling the addition of a stable background signal alongside a reporting signal 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The latter study quantified the fate of particulate matter, but did not provide insights into the transport behavior of these DNA-based tracer particles, which is required when using them as groundwater flow tracers. Horne and co-workers utilized these DNA-based particles as well as pure silica particles in sand columns, , Berea rock, and fractured medium, but no breakthrough curves or extent of recovery was reported. The authors further reported tracer loss, likely caused by the silica dissolution at the applied operating temperatures …”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials, which are of a commensurate size with micro/nano-sized pores in shale, will be considered as an excellent pore marker to light up the targeted pores to improve the pore recognition. In fact, due to their excellent properties, nanomaterials are of wide influence in geoscience, and it was reported they can participate in geological studies as nanosensors, tracers, , in-site catalysts, and surfactants . However, the application of nanomaterials as pore markers for imaging analysis of pore structure in geological materials is rarely reported.…”
mentioning
confidence: 99%